The management of diabetic ketoacidosis at a rural regional hospital in KwaZulu-Natal - Nontobeko F.M. Ndebele; Mergan Naidoo (AOSIS, 2018)
Background: Diabetic ketoacidosis (DKA) is a biochemical triad of hyperglycaemia, ketoacidosis and ketonaemia and one of the potentially life-threatening acute metabolic complications of diabetes mellitus. This study aimed at describing the clinical profile of patients presenting with DKA to a busy rural regional hospital in KwaZulu-Natal. Methods: A retrospective review of clinical notes of patients presenting with DKA to the Emergency Department was performed over a 10-month period. Data included patients' demographic profile, clinical presentation, precipitating factors, comorbidities, biochemical profile, length of hospital stay and outcome. Results: One hundred and five black South African patients above the age of 12 years were included in the study. Sixty-four (60.95%) patients had type 1 diabetes mellitus (T1DM) and 41 (39.05%) patients had type 2 diabetes mellitus (T2DM). Patients with T2DM were significantly older than those with T1DM (52.1 ± 12.4 years vs. 24.4 ± 9.5 years, p < 0.0001). The acute precipitant was identified in 68 (64.76%) cases with the commonest precipitant in T1DM patients being poor adherence to treatment, whereas in T2DM, the most common precipitant was infection. Nausea and vomiting were the most common presenting symptoms with the majority of patients presenting with non-specific symptoms. Fifty-seven (54.29%) cases had pre-existing comorbidities, with higher prevalence in T2DM than T1DM patients. Glycated haemoglobin was severely elevated in the majority of patients. Patients remained hospitalised for an average of 8.9 ± 7.5 days. The mortality rate was 17.14%, and 12 of the 18 deaths occurred in patients with T2DM. Conclusion: The prevalence of DKA was higher in patients with T1DM and those with pre-existing comorbidities. The mortality rate remains alarmingly high in older patients with T2DM.